Clinical outcomes of COVID-19 infection in liver transplant recipients based on vaccination status - Polamraju, Vinathi; Vachharajani, Neeta; Gage, Brian F.; Crippin, Jeffrey S.; Chapman, William C. (Frontiers in Transplantation, 2025)
BackgroundCOVID-19 disease burden has been mitigated by vaccination; however, concerns persist regarding weakened immune responses in liver transplant (LT) recipients. This study investigates COVID-19 outcomes in LT recipients based on vaccination status.MethodsThis single-center retrospective study identified LT recipients with PCR-confirmed COVID-19 infection from 03/01/2020 to 07/31/2023. Logistic regression analyses were conducted, adjusting for age, race, co-morbidities, number of immunosuppressive agents, and infection date.ResultsOf 1,787 registered LT recipients, 361 had confirmed COVID-19 infection. Of those, 136 were unvaccinated and 225 were vaccinated. 13% had 1 vaccine dose, 31% had 2 vaccine doses, and 56% had 3 vaccine doses prior to infection. Logistic regression found higher mortality (p = 0.001) and hospitalization (p = 0.016) rates for older recipients, while those with 3 or more vaccine doses had lower mortality (p = 0.039) and hospitalization (p = 0.008) rates. Chronic kidney disease (CKD) increased risk of hospitalization (p < 0.001). Adjusting for the date when the Omicron variant became locally predominant, the protective effect from 3 or more vaccine doses declined to an OR (95% CI) of 0.58 (0.15–2.23), p = 0.39.ConclusionsThree or more COVID-19 vaccine doses could decrease mortality for LT recipients, particularly older recipients and those with CKD. These individuals may benefit from vaccination and other interventions.